ARTIMAS (Augmented Reality Timun Mas) as a Solution to Enhance Students' Relational Understanding of Vector Material: Feasibility Testing - Pitono, Anindita Putri Canina; Damayanti, Bergitha Putri; Setiaji, Bayu (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2023)
Relational understanding ability is a key skill that affects both the results and processes of learning and is essential for understanding physics subjects, as it helps connect cause and effect of phenomena, including local wisdom such as Timun Mas. Therefore, the aim of this study is to evaluate the feasibility of augmented reality learning media based on Timun Mas as a solution to enhance students' relational understanding of vector material, specifically parabolic motion. The approach method used is ADDIE (Analysis, Design, Development, Implementation, and Evaluation). Feasibility testing was conducted using questionnaires to assess the feasibility of the display and material aspects by practitioners with years of experience in physics and Physics Education students at UNY to evaluate material suitability. The feasibility levels for display, media, and material aspects were calculated using MSI and SBI, with results of 2.548, 2.836, and 2.648, respectively. Therefore, this media is deemed suitable for use as a learning resource.